The low energy signaling network - Tomé, Filipa; Nägele, Thomas; Adamo, Mattia; Garg, Abhroop; Marco-llorca, Carles; Nukarinen, Ella; Pedrotti, Lorenzo; Peviani, Alessia; Simeunovic, Andrea; Tatkiewicz, Anna; Tomar, Monika; Gamm, Magdalena (Frontiers in Plant Science, 2014)
Stress impacts negatively on plant growth and crop productivity, causing extensive losses to agricultural production worldwide. Throughout their life, plants are often confronted with multiple types of stress that affect overall cellular energy status and activate energy saving responses. The resulting low energy syndrome (LES) includes transcriptional, translational, and metabolic reprogramming and is essential for stress adaptation. The conserved kinases SnRK1 and TOR play central roles in the regulation of LES in response to stress conditions, affecting cellular processes and leading to growth arrest and metabolic reprogramming. We review the current understanding of how TOR and SnRK1 are involved in regulating the response of plants to low energy conditions. The central role in the regulation of cellular processes, the reprogramming of metabolism, and the phenotypic consequences of these two kinases will be discussed in light of current knowledge and potential future developments.